Kritik Terhadap Standar Ganda Sistem Pendidikan: Analisis Pemikiran Paulo Freire Terhadap Praktik Penerapan Sistem Pendidikan di Indonesia - Gultom, Benediktus Hasiholan (Integritas Terbuka: Peace and Interfaith Studies, 2024)
Education is a complex and broad topic that involves various concepts, theories, and methods of analysis. Discussions on education are not limited to the teaching and learning processes; they also encompass philosophical issues and policies that are often opaque. The processes of refinement and transformation in education are ongoing, making it a continually engaging topic for discussion. Education plays a crucial role in uniting diverse communities and serves as a powerful tool for the state in building human resources. However, the main challenge lies in determining the appropriate curriculum, considering the complexity and multitude of factors affecting the educational system. This study employs an inductive method to address educational issues in Indonesia by examining the curriculum through the lens of Paulo Freire. By referencing his book Pedagogy of the Oppressed, this research aims to identify the concept of "ideal educational practice" in relation to liberating education. It utilizes both primary and secondary sources to understand the critiques and applications of education in Indonesia. The study analyzes Freire's thoughts and their connection to curriculum practices, culminating in fundamental questions regarding ideal education and the complexities faced. The findings will be presented in a descriptive analysis format, providing a comprehensive overview of educational problems. According to Freire, the domination of power creates oppressive education, contradicting the aims of liberating education. Education should cultivate individual awareness as part of a community, fostering responsibility and contributions to the common good. Educational institutions need to balance the vision of achievement with the mission of student development. All stakeholders—institutions, teachers, and students—must focus on meaningful educational objectives to create a quality educational system.